Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

(1+m)²= (1-m)²+ 4lm,​

Sagot :

The expression is simplified to give 2 ( m² + m + 2Im ) = 0

How to simplify the expression

Given the expression;

(1+m)²= (1-m)²+ 4lm,​

Expand the expression

( 1 +m) ( 1 + m) = ( 1 + m) ( 1 - m) + 4Im

1 + m + m + m² = 1 - m + m - m² + 4Im

collect like terms

1 + 2m + m² = 1 - m² + 4Im

1 - 1 + m² + m² + 2m + 4Im

2m² + 2m + 4lm = 0

simplify

2 ( m² + m + 2Im ) = 0

Thus, the expression is simplified to give 2 ( m² + m + 2Im ) = 0

Learn more about factorization here:

https://brainly.com/question/11579257

#SPJ1

Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.